3d modeling of the peierls transition in TTF-TCNQ organic crystals - Andronic, Silvia (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2015)
The Peierls structural transition in quasi-one-dimensional (Q1D) TTF-TCNQ organic crystals of is studied in the 3D approximation. Two the most important electronphonon interactions are considered. The analytic expression for the phonon polarization operator is obtained in the random phase approximation. The polarization operator as a function of temperature is determined for different values of dimensionless Fermi momentum kF. Different cases are analyzed: kF = 0.59/2 and where the carrier concentration varies and kF = 0.59/2 ± δ, where δ represents the variation of Fermi momentum kF. In all cases, Peierls critical temperature Tp is determined.